RETRACTED: Manufacturing and evaluation of elastic properties of glass fiber reinforced polymers material - Thien, Nguyen Luong; The, Nguyen Tien; Quyet, Tran Nguyen (Vietnam Journal of Mechanics, 2019)
VJMech’s Editors have decided to retract this article because it duplicates significant parts of papers that had previously published in other journals. The authors have misconduct concerning plagiarism of papers without citation.We really apologies to readers of the journal that this was not detected during the submission and review process.